Inconsistency of judicial verdicts in standardizing the threshold of noodweer exces: A review of criminal law and Islamic law - Arsyaddefa Muhammad Fitra Irfani; Abdul Fattaah (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study aims to examine the threshold between self-defense (noodweer) and excessive self-defense (noodweer exces) and its application in Indonesian judicial practice. Using a normative juridical approach through the analysis of selected court decisions, this research compares the regulation of noodweer exces under Indonesian Criminal Law, particularly Article 49 of the Criminal Code (KUHP), and Islamic Criminal Law through the doctrine of daf’u as-shā’il. In Indonesian Criminal Law, noodweer exces eliminates criminal liability when excessive defensive actions are directly caused by severe emotional disturbance (hevige gemoedsbeweging). In contrast, Islamic Criminal Law maintains moral and legal accountability once the limits of proportionality are exceeded, despite the presence of emotional pressure. The findings reveal significant inconsistencies in judicial decisions, particularly in judges’ assessments of proportionality and severe emotional disturbance, resulting in divergent legal outcomes in comparable self-defense cases. This study concludes that such inconsistencies do not stem from the absence of legal norms, but from the lack of objective and uniform standards in determining the threshold of excessive self-defense. Accordingly, this research offers a comparative normative framework to support more consistent and objective judicial reasoning in future self-defense cases.